Progressive collapse analysis through strength degradation and fracture in the Mixed Lagrangian Formulation. - Lavan, O.
The dynamic analysis of progressive collapse faces a great number of obstacles that often lead to the collapse of the analysis prior to the actual analysis of collapse. Hence, the Mixed Lagrangian Formulation that has been shown to be very robust was adopted as a framework to accommodate such analysis. By modifying the loading function and the numerical scheme, the capabilities of this framework were extended to account for strength degradation and fracture, while some insight to its behavior is introduced as well. The examples presented show a very robust and stable behavior of the numerical scheme in terms of the time step size required, even in cases where a sudden fracture takes place.
Keywords: Nonlinear structural dynamics; Fracture; Deterioration; Mixed Lagrangian Formulation; Mixed variational method